Carboxyhaemoglobin in women exposed to different cooking fuels. Issue 5 (May 1991) - Behera, D; Dash, S; Yadav, S P
Abstract : Blood carboxyhaemoglobin levels were estimated by double wavelength spectrophotometry in non-smoking women living in Chandigarh and its environs and related to the cooking fuel they used. Twenty nine used kerosene, 28 biomass fuel, and 30 liquified petroleum gas; the 27 control subjects had not done any cooking for seven days. The carboxyhaemoglobin concentrations were significantly higher in the women using the three types of fuel (mean (SEM) concentration 7.49% [corrected] (0.67%) for kerosene, 15.74% (0.83%) for biomass fuel, and 17.16% (0.62%) for liquified petroleum gas, compared with 3.52% (0.33%) in the control subjects. It is concluded that cooking with any of the three fuels causes indoor air pollution. It is important to have better designed houses with adequate ventilation and stove vents that are cleaned regularly if pollution is to be reduced.